Feature interview with Ranveer Chandra: author of 'white space networking with wi-fi like connectivity', best SIGCOMM paper 2009 - Camp, Joseph; Chandra, Ranveer (Computer Communication Review, 2013)
Ranveer Chandra is a Senior Researcher in the Mobility & Networking Research Group at Microsoft Research. His research is focused on mobile devices, with particular emphasis on wireless communications and energy efficiency. Ranveer is leading the white space networking project at Microsoft Research. He was invited to the FCC to present his work, and spectrum regulators from India, China, Brazil, Singapore and US (including the FCC chairman) have visited the Microsoft campus to see his deployment of the worlds first urban white space network. The following interview captures the essence of his work on white spaces by focusing on his work published in ACM SIGCOMM 2009, which received the Best Paper Award.